2012
DOI: 10.3758/s13414-012-0320-1
|View full text |Cite
|
Sign up to set email alerts
|

Attentional spread in deaf and hearing participants: Face and object distractor processing under perceptual load

Abstract: The case of human deafness constitutes a unique opportunity to examine possible consequences for perceptual processing due to altered sensory experiences. We tested whether deaf-in contrast to hearing-individuals are more susceptible to visual distraction from peripheral than from central face versus object stimuli. The participants were required to classify the gender of a target male or female symbol presented either alone (low perceptual load) or together with three filler symbols (high perceptual load), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
(80 reference statements)
1
14
0
Order By: Relevance
“…These studies consistently demonstrated that the presence of a peripheral visual distractor, incompatible in shape with a concurrent visual target, interferes more with performance in deaf adults than in hearing controls (Chen et al, 2010;Proksch & Bavelier, 2002; but see Hauthal, Neumann, & Schweinberger, 2012). Based on similar interpretations of results in the hearing population, this result may be explained as evidence for increased attentional resources devoted to the peripheral visual field in the deaf population (Lavie, 1995;Lavie & Cox, 1997;Maylor & Lavie, 1998).…”
Section: Reorganization Of Stimulus-driven Control In Early Bilateralmentioning
confidence: 60%
“…These studies consistently demonstrated that the presence of a peripheral visual distractor, incompatible in shape with a concurrent visual target, interferes more with performance in deaf adults than in hearing controls (Chen et al, 2010;Proksch & Bavelier, 2002; but see Hauthal, Neumann, & Schweinberger, 2012). Based on similar interpretations of results in the hearing population, this result may be explained as evidence for increased attentional resources devoted to the peripheral visual field in the deaf population (Lavie, 1995;Lavie & Cox, 1997;Maylor & Lavie, 1998).…”
Section: Reorganization Of Stimulus-driven Control In Early Bilateralmentioning
confidence: 60%
“…Deaf individuals also appear to provide a caveat for perceptual load theory, due to their apparently enhanced visual capacity limits. High perceptual load, sufficient to eliminate distractor interference in hearing participants, had no effect on deaf participants (Hauthal, Neumann, & Schweinberger, 2012). In contrast, adults with attention deficit hyperactivity disorder (ADHD) experienced increased distraction as compared to controls, but increasing perceptual load was found to be equally effective at reducing distractor interference for both groups (Forster, Robertson, Jennings, Asherson, & Lavie, 2014).…”
Section: Individual Differences Under Loadmentioning
confidence: 96%
“…Several studies have manipulated load to test attentional capacity differences across development (Couperus, 2011;Huang-Pollock, Carr, & Nigg, 2002;Maylor & Lavie, 1998), autism spectrum disorder (e.g., Remington, Swettenham, & Lavie, 2012), deaf individuals (e.g., Hauthal, Neumann, & Schweinberger, 2012), and other differences between different groups (see Murphy et al, 2016 for a review). The rationale goes as follows: if a group has less attentional capacity than the regular population, then these individuals are expected to be undistracted even under small set size displays or in medium-load, compared to a control group.…”
Section: Automaticity Versus Enhanced Attentional Capacitymentioning
confidence: 99%
“…That is, due to their enhanced attentional capacity, leftover resources are expected to remain from the task even in a high-load presentation. For example, in the study of Hauthal et al (2012), manipulating load via set size affected distractor interference in hearing participants, but had no effect on deaf participants. Hauthal and colleagues then concluded that auditory deprivation may result in enhanced visual attentional capacities.…”
Section: Automaticity Versus Enhanced Attentional Capacitymentioning
confidence: 99%